EVALUASI FUNGSI BENDUNG DAN PERENCANAAN KEMBALI BENDUNG KATULAMPA - Fardiaz, Dion Kartino; Purwitaningtyas, Rita; Wahyuni, Sri Eko; Kodoatie, Robert J. (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2015)
As Jakarta developed into a metropolitan city, flood problems become the center of attention for its citizens and the government of Jakarta. Ciliwung River is one of the significant contributors to flood discharge in Jakarta. Flood control in Jakarta area requires a very hard effort, considering the geological conditions which is an area of the basin and hydrological conditions are very vulnerable to inundation because bypassed by many rivers from upstream. Changes in land use that was once empty land converted to settlements, housing, and the building also has occurred both in the upstream and downstream along the rivers that pass through Jakarta. After an evaluation of watershed and watershed Krukut Sunter which is around Ciliwung watershed, it was found that there were streams of the watershed around the exit and entry into the Ciliwung watershed. These rivers flood contributed by ± 25% of the Ciliwung watershed resulting in widespread inundation in Jakarta increases. One of the efforts to control flooding in Jakarta is the construction of weirs Katulampa which serves as an early information system to flooding Ciliwung will enter Jakarta. From the evaluation of the function obtained Katulampa weir water level to Alert 1 is 200-250 cm to estimate flood discharge using HEC-HMS at 733 m3 / s. Data on the water level in the dam Katulampa estimates that approximately 9-10 hours later flood will arrive in Jakarta. The ability of the dam to divert water when it reaches Alert 1 of 7% of the flood discharge through the doors retrieval. In order to optimize the function of the weir and re-plan the weir, the initial step is the hydrological analysis with the result that be discovered gauge the dependable discharge, needs water discharge and flood discharge. In the Katulampa weir planning dependable discharge used is the discharge with probability 80%. Water needs value to fulfill the irrigation water requirement is 1.87 liters / sec / ha or water needs discharge for water irrigation is 6.03 m3 / sec. Flood discharge by the method of HEC-HMS for the return period of 25 years at 733.90 m3 / sec is used as the basis to design the main building weirs. Katulampa weir using high lighthouse beacon round with effective width of 2.5 m and 95.43 m. Bags of mud along the channel with a width of 62.5 m at 4.75 m channel basis. Katulampa weir construction planned at a cost of ±4,193,000,000.00 billion rupiah, and planned implementation time ± 168 working days.